Determination Functions of Magnetic Fields Saddle-type DY - Matuliauskas, R. (Elektronika ir Elektrotechnika, 2008)
The theoretical method for the determination of functions of magnetic fields are only used in the case of simple DY constructions. According to newly developed methods these magnetic field functions are needed to calculate aberrations’ parameters found to saddle– type DY. Ill.1, bibl 7 (in English; summaries in English, Russian and Lithuanian).